Leptin Regulates Proliferation and Apoptosis in Human Prostate - Eduardo Leze; Jorge Luiz Alves-Pereira; Sicilia Colli; Fernanda Silveira Cavalcante; Francisco José Sampaio; Cristiane da Fonte Ramos (The Scientific World Journal)
This paper aimed to evaluate the leptin role on the cellular proliferation and the expression of fibroblast growth factor 2, aromatase enzyme, and apoptotic genes in the human prostate tissue. Methods. Fifteen samples of hyperplasic prostate tissue were divided in four symmetric parts maintained in RPMI medium supplemented with 10% fetal bovine serum, 1 ng/mL of gentamicin, and added with 50 ng/mL leptin (L) or not (C). After 3 hours of incubation, gene expression was evaluated by real time RT-PCR. Cellular proliferation was evaluated by immunohistochemistry for PCNA. Results. The leptin treatment led to an increase cellular proliferation (C=21.8±0.5; L=64.8±0.9; P<0.0001) and in the expression of Bax (C=0.4±0.1; L=0.9±0.2; P<0.05) while Bcl-2 (C=19.9±5.6; L=5.6±1.8; P<0.05), Bcl-x (C=0.2±0.06; L=0.07±0.02; P<0.05), and aromatase expressions (C=1.9±0.6; L=0.4±0.1; P<0.04) were significantly reduced. Conclusion. Leptin has an important role in maintaining the physiological growth of the prostate since it stimulates both cellular proliferation and apoptosis, with the decrement in the aromatase gene expression.